CROSSING THE BOUNDARIES OF IDENTITY: A CONTEXTUAL HERMENEUTICS OF JOHN 4:7-15 IN THE CONTEXT OF MIGRATION THEOLOGY IN INDONESIA - Silaen; Junita Batubara (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This paper focuses on a contextual hermeneutical analysis of John 4:7–15 in relation to the theology of migration in Indonesia. Migration as a social phenomenon is a complex reality caused by various factors, such as economics, natural disasters, and developments in transportation and information technology that enable large-scale human mobility. In the Indonesian context, this phenomenon has been going on for a long time and continues to have significant social, cultural, and theological impacts. Through a contextual hermeneutical approach, this study seeks to explore the theological meaning of the conversation between Jesus and the Samaritan woman as a model for understanding contemporary theology of migration. The text of John 4:7–15 is understood as an event that transcends social, cultural, and identity boundaries. Jesus' dialogue with the Samaritan woman demonstrates an effort to break down discriminatory barriers between different groups and affirms the universal nature of love and salvation offered by Christ. In the context of the theology of migration in Indonesia, this passage reflects the values ​​of hospitality and inclusivity that form the basis for forming a community open to differences. Hospitality is understood not only as an attitude of welcoming the presence of strangers, but also as a reflection of God's love that erases the boundaries between "us" and "them." Meanwhile, inclusivity emphasizes the importance of social and spiritual integration that values ​​diversity as part of unity in Christ. This study demonstrates that the church in Indonesia needs to emulate Jesus' attitude in building relationships across identities and fostering solidarity with migrants who often experience discrimination. Through contextual hermeneutics, the text of John 4:7-15 is read not only as a historical narrative but also as a theological call to present God's love amidst the realities of modern migration. This study confirms that a biblically based theology of migration can offer a new paradigm that encourages the church to become a space of hospitality and reconciliation for all people regardless of social, ethnic, or cultural background.